MODELING OF PROCESSES OF SHRINKABLE DEFECTS FORMATION AT PRODUCTION OF CASTINGS - K. V. Kobyakov; Yu. A. Nikolaychik (Литьë и металлургия)
Analysis of ways of increase of the feeding discards efficiency on the basis of results of computer modeling of processes of shrinkable defects formation in Schwartz’s test is carried out.